Penerapan Pendekatan Teaching At The Right Level (TARL) Untuk Meningkatkan Motivasi Dan Pemahaman Konsep Bilangan Berpangkat Di Kelas VIII - Lania, Renna; Soraya, Ratna; Nasution, Cholizah (Education Journal : Journal Educational Research and Development, 2024)
This study is motivated by the low motivation and conceptual understanding among the eighth-grade students at UPT SMP Negeri 8 Medan. The existing teaching methods, which do not address the students' needs or sufficiently motivate them, have led to a poor grasp of mathematical concepts, particularly in exponentiation. The "Teaching at the Right Level" (TaRL) approach, which is not confined to grade levels, can accommodate various student characteristics and enhance both motivation and conceptual understanding. Conducted over two cycles, this study aims to improve motivation and understanding of exponentiation concepts. Motivation data were collected through questionnaires, while understanding of the concepts was assessed via written tests, with both types of data analyzed quantitatively. The findings reveal an increase in motivation from 70.95% in Cycle I to 77.9% in Cycle II, and an improvement in understanding of exponentiation concepts from 80.63% in Cycle I to 86.9% in Cycle II.